Comprehensive chemical profile and quantitative analysis of the Shabyar tablet, a traditional ethnic medicine prescription, by ultra‐high‐performance liquid chromatography with quadrupole‐orbitrap high‐resolution mass spectrometry. Issue 13 (19th April 2022) - Yan, Yahui; Abdulla, Rahima; Liu, Xiaoyan; Li, Shuping; Aisa, Haji Akber
Abstract : The Shabyar tablet is commonly used as a traditional ethnic medicine prescription for the treatment of night blindness, poor vision, and headaches. However, the chemical components of the Shabyar tablet have not been holistically explored, which seriously hinders the discovery of the activity. This study qualitatively and quantitatively investigated the overall chemical profile of the Shabyar tablet using ultra‐high‐performance liquid chromatography hyphenated with quadrupole‐orbitrap high‐resolution mass spectrometry. Altogether, 170 chemical components, including 59 flavonoids, 78 organic acids, 12 anthranones, three anthraquinones, one naphthalene, and 17 other compounds were tentatively identified and attributed, with 40 among these being unambiguously characterized in comparison with their corresponding authentic standards. To further determine the major representative constituents of the Shabyar tablet, a quantitative method was used for the simultaneous analysis of 33 characteristic components in Shabyar samples. The results were validated in terms of linearity, precision, repeatability, stability, and recovery. This newly developed approach could be successfully employed for evaluating the holistic quality of crude extracts and Chinese medicines in the Shabyar compound tablet and provide a solid chemical foundation for additional investigations on in vivo pharmacodynamics and therapeutic mechanisms to identify the potential effective components of traditional medicines.